Role of Gender in Improvement of Depressive Symptoms Among Patients Undergoing Cervical Spine Procedures - Elliot D.K. Cha; Conor P. Lynch; James M. Parrish; Nathaniel W. Jenkins; Cara E. Geoghegan; Caroline N. Jadczak; Shruthi Mohan; Kern Singh (Neurospine, 2021)
Objective There is a scarcity of research evaluating gender differences in depressive symptoms among patients undergoing cervical surgery. This study investigated gender differences with regard to depressive symptom severity, measured by Patient Health Questionnaire-9 (PHQ-9), in patients following anterior cervical discectomy and fusion (ACDF) or artificial disc replacement (ADR). Methods A prospectively maintained surgical registry was retrospectively reviewed for eligible spine surgeries. Depressive symptom severity was evaluated by PHQ-9 at both preand postoperative timepoints (e.g. , 6 weeks, 12 weeks, 6 months, 1 year, and 2 years). A chi-square test and Student t-test evaluated differences between the gender for demographic and operative variables where appropriate. Differences between the gender subgroup mean PHQ-9 scores were assessed using a t-test pre- and postoperatively (e.g. , 6 weeks, 12 weeks, 6 months, and 1 year) and a paired t-test was used to assess differences from preoperative scores at each postoperative time point. Results A total of 170 subjects underwent 125 ACDFs and 45 ADRs. Both pre- and postoperative timepoints demonstrated no significant differences between mean PHQ-9 scores by gender. Female patients demonstrated statistically significant improvement in PHQ-9 scores at 6 weeks, and 12 weeks, but not through 2 years. Male patients demonstrated statistically significant improvement in PHQ-9 scores at 6 weeks, 12 weeks, 6 months, 1 year, and 2 years. Conclusion Although there were no significant differences between mean PHQ-9 score between the genders, there was a difference in magnitude of improvement. Females had a significant improvement in depressive symptom severity over baseline at the 6- and 12-week timepoints only, whereas males had significant improvement through 2 years postoperatively.